Anode modification by biogenic gold nanoparticles for the improved performance of microbial fuel cells and microbial community shift. (December 2018) - Wu, Xiayuan; Xiong, Xiaomin; Owens, Gary; Brunetti, Gianluca; Zhou, Jun; Yong, Xiaoyu; Xie, Xinxin; Zhang, Lijuan; Wei, Ping; Jia, Honghua
Highlights: BioAu modification significantly improved the electricity generation of MFCs. Better performance was achieved with BioAu/MWCNT nanohybrids as the modifier. BioAu/MWCNT had higher electrocatalytic activity and affinity towards exoelectrogens. Electroactive bacteria in the modified electrode biofilms shared higher proportions. The class Negativicutes might be specifically enriched by Au nanoparticles. Abstract: In this study, carbon cloth anodes were modified using biogenic gold nanoparticles (BioAu) and nanohybrids of multi-walled carbon nanotubes blended with BioAu (BioAu/MWCNT) to improve the performance of microbial fuel cells (MFCs). The results demonstrated that BioAu modification significantly enhanced the electricity generation of MFCs. In particular, BioAu/MWCNT nanohybrids as the modifier displayed a better performance. The MFC with the BioAu/MWCNT electrode had the shortest start-up time (6.74 d) and highest power density (178.34 ± 4.79 mW/m 2 ), which were 141.69% shorter and 56.11% higher compared with those of the unmodified control, respectively. These improvements were attributed to the excellent electrocatalytic activity and strong affinity towards exoelectrogens of the BioAu/MWCNT nanohybrids on the electrode. High throughput sequencing analysis indicated that the relative abundance of electroactive bacteria in the biofilm community, mostly from the classes of Gammaproteobacteria and Negativicutes, increased after anode modification.